The Effectiveness of the HYPO Method (Hypnobreastfeeding and Oxytocin Massage) with Breast Milk Expenditure in Postpartum Post-Sc Mothers at RSIA Cahaya Bunda Cirebon City in 2023 - Fikriyyah, Dinah; Mutya Sari, Vianty; Aliah, Nur (Ann Publisher, 2024)
With all these factors, it helps mothers and their families, especially their husbands, to be able to do oxytocin massage and hypnosis so that they can release the hormones prolactin and oxytocin to trigger milk release. (Josefa, 2013). The importance of exclusive breastfeeding can be seen from the role of the world, namely in 2006 the World Health Organization (WHO) issued Child Growth Standards which were then applied throughout the world whose contents emphasized the importance of giving only breast milk to babies from birth to 6 months of age. (Prasetyono, 2009). Apart from that, the importance of breastfeeding was also seen in world events, namely the World Breastfeeding Week in August 2008, The World Alliance For Breast Feeding Action (WABA) chose the theme Mother Support: Going For the Gold. The meaning of the theme is a movement to invite everyone to increase support for mothers to provide their babies with gold standard food. This study uses comparative research. That is using a control group design research. In this study there were two groups, namely the control group without treatment and the intervention group with treatment, then the results were measured through observation before being processed in the SPSS test. In the control group without intervention, the results of the majority of breastfeeding were ≤ 20 ml as much as 95%. Meanwhile, in the intervention group with the treatment, there was a majority of > 20 ml of breast milk expenditure, as much as 90%. The average value of breastfeeding was 34.50 ml for the intervention group, 15 ml for the control group. There is an effectiveness between the HIPO method (Hypnobreastfeeding and Oxytocin Massage) and milk production in postpartum post SC mothers at RSIA Cahaya Bunda Cirebon with a significance value of 0.000 <0.05.